Analisis Kepuasan Sekolah Mitra Terhadap Mahasiswa Praktik Lapangan Kependidikan FKIP UMMY Tahun 2024 - Hana Adhia; Redo Andi Marta; Helvita Roza; Roza Zaimil; Risza Dwiputri; Ikhwan (LPPM Universitas Ekasakti, 2024)
Using a qualitative descriptive research approach and percentage calculations, this research examines the level of satisfaction of partner schools with Educational Field Practice (PLK) students. The research focuses on the findings of a satisfaction level analysis conducted at the Faculty of Teacher Training and Education, Mahaputra Muhammad Yamin University for PLK Mitra School students in the Odd Semester 2024–2025. The concepts, principles and policies of the 2022 PLK guidebook form the basis of this study approach. PLK has eight partner schools, including seven SMPN and one SMAN in public schools in Solok City and Regency. The results of the Partner School's level of satisfaction with educational field practice students, based on comprehensive data analysis, show that the Partner School's satisfaction with PLK on student ethics was found to be very satisfied (87.5%), communication skills were found to be less satisfied (75%), use of technology was satisfied (84.35%), collaboration was satisfied (81.25%), self-development was less satisfied (75%), and teaching competence was satisfied (81.25%). Therefore, it can be said that in general respondents prefer or appreciate PLK students based on these indications. By planning PLK activities, this will have an impact on the development of schools, tutors and PLK students.